Analisis Kepuasan Pengguna Game Online Mobile Legend Menggunakan Metode Technology Acceptance Model (TAM) - Elza Susana Tupamahu; Leliyanah Leliyanah; Dahlia (Journal of Students‘ Research in Computer Science, 2024)
Playing online games has become a common activity in society. Mobile Legends is an online game application that is equipped with various component features. The focus of the research is to understand the perception of ease, usefulness, desires and attitudes of users towards the Mobile Legends application. The research method is the Technology Acceptance Model (TAM) and the variables measured include perceived ease of use, perceived usefulness, user desires (Behavioral Intention To Use) and attitude towards use. The results of the research show a partial hypothesis test using the t test, it was found that perceived convenience had no effect but perceived usefulness and user desires had an effect on attitudes towards use. In testing the hypothesis simultaneously through the F and R-Square tests, it was revealed that perceived convenience, perceived usefulness and user desires contributed 62.1% to the formation of usage attitudes.